2015
DOI: 10.1109/jsen.2015.2391106
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Detection of Vitamin D<sub>3</sub> Compounds Using a Cylindrical Optical Microcavity

Abstract: This paper explores the detection of vitamin D 3 (VD3) using a fluorescent microcavity sensor. There is currently a high demand for measurement and analysis of this vitamin, whose deficiency may result in several different pathologies; however, the standard methods, predominantly based on mass spectroscopy and liquid chromatography require large equipment and must be done remotely. In contrast, measurement of solvent concentrations via microcavity-based optical systems can be sensitive to small changes and req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…This work demonstrated that microgoblets can be used as biolasers for the detection of anti‐2,4‐Dinitrophenol . Other examples of biosensing include polystyrene microspheres embedded with CdSe/ZnS QDs for thrombin detection , dye‐doped polymer coated microcapillaries for detecting Vitamin D Binding Protein , fluorescent microspheres for the detection of unlabeled oligonucleotide targets , and the multiplexed quantification of ovarian cancer markers . In terms of reaching the same single‐molecule detection capability of passive resonators, a self‐referenced and self‐heterodyned WGM Raman microlaser was recently demonstrated .…”
Section: Applicationsmentioning
confidence: 98%
“…This work demonstrated that microgoblets can be used as biolasers for the detection of anti‐2,4‐Dinitrophenol . Other examples of biosensing include polystyrene microspheres embedded with CdSe/ZnS QDs for thrombin detection , dye‐doped polymer coated microcapillaries for detecting Vitamin D Binding Protein , fluorescent microspheres for the detection of unlabeled oligonucleotide targets , and the multiplexed quantification of ovarian cancer markers . In terms of reaching the same single‐molecule detection capability of passive resonators, a self‐referenced and self‐heterodyned WGM Raman microlaser was recently demonstrated .…”
Section: Applicationsmentioning
confidence: 98%
“…Even if a single bio-particle of nanoscale is locally attached to the cavities’ surface, it would also rearrange the electric field distribution because of highly enhanced light-particle interaction. Recently, much research attention has been put on the WGM-based detection of single particles, such as virus, DNA and single proteins [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. Some reviews had made detailed descriptions of the theories and the recent biosensing applications of optical microresonators [ 27 , 28 , 67 , 68 ].…”
Section: Optofluidic Microcavities For Biosensorsmentioning
confidence: 99%
“…An external light source (white source or tunable laser) is used to couple photons into the cavities by the taper fiber or the waveguide. By monitoring the shift or splitting the resonant peaks of transmission spectra, analyte concentration or molecule attaching can be detected [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. As the optical confinement elements, the cavities with high Q factor would greatly enhance the light-matter interaction and would result in high sensitivity.…”
Section: Optofluidic Microcavities For Biosensorsmentioning
confidence: 99%
“…A physisorption-based surface functionalization process, using bovine serum albumin (BSA) directly deposited onto the sensor surface and subsequently cross-linked with antibodies [107], has been used with fluorescent polystyrene microspheres, while a PE-based surface functionalization process has also been used with both fluorescent polystyrene microspheres [108] and glass capillaries [118,119], demonstrating the applicability of such approach for biosensing applications involving whispering gallery modes. Biomolecule immobilization, non-specific binding, and specific orientation The deposition of either silanes or PE multilayers is merely the first step of a complex process.…”
Section: Physisorptionmentioning
confidence: 99%